Durability and mechanical properties of cement concrete comprising pozzolanic materials with alkali-activated binder : A comprehensive review - Tayeh, Bassam A.; Hamada, Hussein Mahmood; Almeshal, Ibrahim; Badorul Hisham, Abu Bakar (Elsevier Ltd, 2022)
The disintegration of concrete structures made of ordinary Portland cement (OPC) is a worrying topic of increasing significance. The trend for reusing waste products or industrial by-products to reduce the amount of OPC in concrete constructions has become an important task for industries and research institutions. Although OPC is an essential ingredient for concrete and is immensely popular, it greatly ‎contributes to the release of a massive quantity of CO2 into the atmosphere. To decrease the ‎increasing CO2 emission, scholars and researchers in the construction industry and ‎academic institutions have exerted efforts to adopt alternative sustainable binders using ‎pozzolanic materials, such as metakaolin, fly ash, slag, rice husk ash, and ‎palm oil fuel ash, combined with alkali-activator (AA). Many researchers have ‎stated that AA alumina-silicate (Al2SiO2) materials can produce convincing mechanical ‎and durability properties, such as compressive strength, splitting tensile strength, and ‎modulus of elasticity, in cement concrete at an early age with low CO2 emission and ‎energy consumption. Most researchers have reported that concrete containing pozzolanic materials and alkali-activated binder (AAB) has better durability than conventional concrete, while others call for further studies. According ‎to previous studies, this research assesses the present studies on the mechanical and ‎durability properties of cement concrete produced from the AAB related to the ‎pozzolanic materials. Furthermore, few possible studies have been recommended in the ‎future‎.